Vaccine Financing for the Treatment of Covid-19 of Banking Agencies’ in Empowering Small and Medium Health Institution at Aceh - Yusri Yusri; Tan Kamello; Husni Husni; Iman Jauhari (Indian Journal of Forensic Medicine & Toxicology, 2021)
The purpose of this article is to explain the vaccine financing for the treatment of covid-19 of BankingAgencies in an effort to empower Small and Medium Institution in Aceh. This study applies qualitativelegal methods with a descriptive-analytical approach. The results of the study indicate that the vaccinefinancing for the treatment of covid-19 and the existence of the Banking Agencies is instrumental in effortsto empowerment SMHi and covid-19 treatment, but the quantity of SMHi that can be financed very limited.Only a small proportion of SMHi can obtain loan facilities from bank agencies. In conclusion, bank agenciesstill not yet play the important role in empowerment the micro, small and medium Health Institution in Aceh.